Developing methods for forming brand strategy of higher educational institution - Степуріна, Світлана Олександрівна; Сергієнко, Олена Андріанівна; Білоцерківський, Олександр Борисович (Agenda Publishing House, 2017)
Статтю присвячено розробці та застосуванню методичних засобів щодо формування стратегії розвитку бренду ВНЗ, на підставі методів економетричного моделювання та кластерного аналізу, що дає змогу виявити найбільш впливові фактори формування лояльності споживачів освітніх послуг ВНЗ.

The article is devoted to the development of some methodical approaches to formation of the brand development strategy of Universities, on the basis of econometric modeling and cluster analysis methods, which allow to identify the most influential factors for consumers loyalty formation of educational services of higher educational institutions.
Методичні засоби розробки стратегії формування бренду вищого навчального закладу
Keywords: маркетингова стратегія; бренд; потенціал вищого навчального закладу; marketing strategy; brand; potential of a higher educational establishment